Humanin promotes tumor progression in experimental triple negative breast cancer - Moreno Ayala, Mariela Alejandra (2020)
Humanin (HN) is a mitochondrial-derived peptide with cytoprotective effect in many tissues. Administration of HN analogs has been proposed as therapeutic approach for degenerative diseases. Although HN has been shown to protect normal tissues from chemotherapy, its role in tumor pathogenesis is poorly understood. Here, we evaluated the effect of HN on the progression of experimental triple negative breast cancer (TNBC). The meta-analysis of transcriptomic data from The Cancer Genome Atlas indicated that HN and its receptors are expressed in breast cancer specimens. By immunohistochemistry we observed up-regulation of HN in TNBC biopsies when compared to mammary gland sections from healthy donors. Addition of exogenous HN protected TNBC cells from apoptotic stimuli whereas shRNA-mediated HN silencing reduced their viability and enhanced their chemo-sensitivity. Systemic administration of HN in TNBC-bearing mice reduced tumor apoptotic rate, impaired the antitumor and anti-metastatic effect of chemotherapy and stimulated tumor progression, accelerating tumor growth and development of spontaneous lung metastases. These findings suggest that HN may exert pro-tumoral effects and thus, caution should be taken when using exogenous HN to treat degenerative diseases. In addition, our study suggests that HN blockade could constitute a therapeutic strategy to improve the efficacy of chemotherapy in breast cancer.